Comparison of Net Benefits of Incentive-Based and Command and Control Environmental Regulations: - O'Ryan, Raúl; Sánchez, José Miguel (World Bank, 2012)
The ambient permit system proposed in the literature for cost-effective pollution reduction is difficult to implement and may result in lower net benefits than using another instrument. The article develops a model for comparing the environmental net benefits of three policy instruments for Santiago, Chile, when the policy problem is to meet a given ambient quality standard. Two market-based instruments—the ambient permit system and a simpler emission permit system—are examined along with an emission standard, a command and control instrument usually favored by regulators. Both emission permit system and emission standard are costlier than the ambient permit system, sometimes in large part because they improve ambient emission concentrations beyond the required target in much of the city, but the ambient permit system requires a lower degree of control to comply with the standard. The somewhat costlier emission permit system and emission standard provide much higher net benefits than the ambient permit system when the health benefits of their "excessive" air quality improvements are taken into account. These benefits are different from the fact that an ambient permit system is administratively costlier to implement.